2020
DOI: 10.1097/hs9.0000000000000350
|View full text |Cite
|
Sign up to set email alerts
|

Beyond DNA Damage: Exploring the Immunomodulatory Effects of Cyclophosphamide in Multiple Myeloma

Abstract: The alkylating agent cyclophosphamide has been used in the treatment of multiple myeloma for over 60 years. At low doses, cyclophosphamide also has significant immunomodulatory activity, which can be used to modify the immunosuppressive tumor microenvironment in order to augment responses to existing therapies. Immune-mediated therapies are becoming more widespread in modern approaches to myeloma treatment. In this review, we discuss the effects cyclophosphamide has on the immune system, and how it can be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 109 publications
(204 reference statements)
2
21
0
Order By: Relevance
“…Many multiple myeloma standard-of-care drugs act directly by killing the tumor and remodeling the TME to break cycles of tumor survival. For example, the DNA-alkylating agent cyclophosphamide (Cy), in addition to inducing DNA damage, preferentially kills regulatory T cells (Treg), induces an acute secretory activating phenotype in tumor cells stimulating phagocytic activity, and promotes immunogenic tumor cell death (ICD), all of which can boost immunotherapy (16). Furthermore, thalidomide and derivatives ( immunomodulatory imide drugs, IMiD), also known as Cereblon (CRBN) modulators, have pleiotropic effects on the immune system that include upregulating cytokine production and potentiating growth and survival of effector T lymphocytes while reducing Treg expansion and function (17,18).…”
mentioning
confidence: 99%
“…Many multiple myeloma standard-of-care drugs act directly by killing the tumor and remodeling the TME to break cycles of tumor survival. For example, the DNA-alkylating agent cyclophosphamide (Cy), in addition to inducing DNA damage, preferentially kills regulatory T cells (Treg), induces an acute secretory activating phenotype in tumor cells stimulating phagocytic activity, and promotes immunogenic tumor cell death (ICD), all of which can boost immunotherapy (16). Furthermore, thalidomide and derivatives ( immunomodulatory imide drugs, IMiD), also known as Cereblon (CRBN) modulators, have pleiotropic effects on the immune system that include upregulating cytokine production and potentiating growth and survival of effector T lymphocytes while reducing Treg expansion and function (17,18).…”
mentioning
confidence: 99%
“…The alkylating agent cyclophosphamide has been used in the treatment of MM for over 60 years and, at low doses, it also presents significant immunomodulatory activity [ 193 ]. In this sense, treatment of different tumor models with mafosfamide (a chemical compound related to cyclophosphamide) or cyclophosphamide induces CALR translocation [ 181 , 182 ] and the release of HMGB1 [ 181 ], both of them being surrogate ICD markers.…”
Section: Drugs With Immune-stimulating Activity In Multiple Myelommentioning
confidence: 99%
“…While the alkylating effect is predominant when cyclophosphamide is used at high doses, more recent studies have observed that cyclophosphamide at lower doses, also described as metronomic dosing, has significant immunomodulatory activity [ 62 , 63 ]. Although there is no clear borderline between low and high doses, new roles for the metronomic use of cyclophosphamide are being explored in the context of immune-mediated therapies, particularly immunomodulating agents.…”
Section: Current Use Of “Old” Alkylating Agentsmentioning
confidence: 99%